A Discussion of Real Food, Real Facts: Processed Food and the Politics of Knowledge by Charlotte Biltekoff - Legun, Katharine; Fairbairn, Madeleine; Frohlich, Xaq; Hendrickson, Mary; Blancaneaux, Romain; Asiedu Sefa, Marilyn; Setsoafia, Eugene; Tanferri, Mylène (The International Journal of Sociology of Agriculture and Food, 2025)
On November 25th 2024, the RC-40 book club held a meeting to discuss Real Food, Real Facts: Processed Food and the Politics of Knowledge by Charlotte Biltekoff. This review is the product of our collective discussion.